LA CULTURA COMO OPERADOR EN LAS OPCIONES METODOLÓGICAS EN EDUCACIÓN MATEMÁTICA - Mometti, Carlos (2026)
This paper aims to present a case study about the influences that culture exerts on the methodological choices of a pedagogue teacher when developing her practice in primary education. For this purpose, we used the teaching practice in primary education as a context, giving special attention to teaching Mathematics in the five early years. To access the methodological choices of the subject teacher of this research, we used a semi-structured interview as a source of information, from which analysis data were generated through ipsis litteris transcription and discursive analysis from the French perspective. As a result of this study, we realized that the cultural operator was present in the methodological choices made by the teacher, mainly associated with her emotions and elements of her story. In addition, emotionality was perceived as an intrinsic element of the emotion/quality of teaching/choice of method triad. The present study opened a door for us to studies related to the methodological choices of pedagogical teachers in the first years of elementary school, as well as to the understanding of the fact that culture can be an essential operator of tension in the teaching process.